Rangeland Ecosystem Service Procedure (RESP) for quantifying and valuing rangeland ecosystem service gains - Bayliss, J. (Rangeland Stewardship Council, 2025)
A presentation on the a rangeland ecosystem procedure to capture impacts of investments in rangelands restoration, in support of the development of a global rangelands standard.